Validation of the Red Flags Index for Early Diagnosis of Crohn’s Disease: A Prospective Observational IG-IBD Study Among General Practitioners - Fiorino, Gionata; Bonovas, Stefanos; Gilardi, Daniela; Di Sabatino, Antonio; Allocca, Mariangela; Furfaro, Federica; Roda, Giulia; Lenti, Marco V; Aronico, Nicola; Mengoli, Caterina; Angeli, Enzo; Gaffuri, Nicola; et al. (Journal of Crohn's and colitis, 2020)
Abstract Introduction Diagnostic delay >12 months is frequent in Crohn’s disease [CD]. Recently, the International Organization for Inflammatory Bowel Disease [IO-IBD] developed a tool to identify early CD and reduce diagnostic delay. Subjects with an index ≥8 are more likely to have suspected CD (odds ratio [OR] 205, p <0.0001). We aimed to validate this questionnaire at the community level in patients seen by the general practitioners [GPs] in two large areas of Lombardy, Italy. Methods Consecutive adult patients referring to the GP were screened. The GPs administered the Red Flags [RF] questionnaire to the eligible patients. All patients were referred to the nearest participating centre to confirm or exclude the diagnosis of CD. Sensitivity, specificity, and positive and negative predictive values [PPV, NPV] of the RF index [RFI] were calculated. Patients lost to follow-up after the first gastroenterological visit were analysed using a non-responder imputation, assuming they were negative for CD diagnosis. Results From November 2016 to November 2019, 112 patients were included. A total of 66 subjects [59%] completed the study after the first gastroenterological visit. The prevalence of CD was 3.6% in the study population [4/112]. The RF index had 50% sensitivity, 58% specificity, 4% PPV, and 97% NPV. A combined diagnostic strategy with faecal calprotectin [FC] [RFI ≥8 and/or FC >250 ng/g] resulted in significantly improved accuracy: sensitivity 100% [29–100%], specificity 72% [55–85%], PPV = 21% [5–51%], NPV = 100% [88–100%]. Conclusions The RF Index combined with FC is a valid tool to identify patients with high probability of having CD at early stage.